Comparative study on mechanical behavior of ASS 316L for low and high temperature applications. (2019) - Harshini, Dharanikota; Haq, Ahsan ul; Buddi, Tanya; Ajay Kumar, K.; Anitha Lakshmi, A.
Abstract: Austenitic Stainless-Steel 316L is among the significant ASS grades which are most commonly used in various modern industries. It has greater resistance to corrosion in the ordinary atmosphere as well as in extreme environments such as salt water and environments where resistance to pitting and chloride corrosion is required. While performing well when exposed to elevated temperatures, it can also maintain its quality toughness and strength at negative temperatures which makes it as an exceptional choice for applications such as water treatment, marine, nuclear, aerospace and automobile industries. Therefore, present study focused on evaluating and comparing the mechanical properties namely ultimate tensile strength (UTS), 0.2% of yield quality (YS) and percentage elongation from the experimental data acquired from the uniaxial isothermal tensile tests performed at sub-zero temperatures (0 °C, −25 °C & −50 °C) with a range of cross head speeds and at elevated temperatures (750 °C, 825 °C & 900 °C) in three orientations (0, 45, 90) degrees to the rolling direction. The influence of temperature and strain rate on the responses has been resolved and the comparison has been made at extreme temperatures.